Multinational Corporate Pricing Strategy in the Developing Countries: A Reply - Leff, Nathaniel H. (Journal of International Business Studies, 1977)
I am grateful to Professors Pedro Belli and Harsharanjeet Singh Jagpal for their comments, which provide a welcome opportunity to clarify some points in my paper.1 I will first discuss the issues raised by Professor Jagpal, and subsequently those raised by Professor Belli.